In-vitro cytocompatibility of dental resin monomers on osteoblast-like cells. (October 2017) - Kraus, Dominik; Wolfgarten, Markus; Enkling, Norbert; Helfgen, Ernst-Heinrich; Frentzen, Matthias; Probstmeier, Rainer; Winter, Jochen; Stark, Helmut
Abstract: Objectives: Dental resin-based materials are widely used in modern dentistry. Especially, resin cements enjoy great popularity and are utilized in many applications. Nevertheless, monomers could be released from the resinous matrix, thus interact with surrounding tissues, cause adverse biological reactions and may lead in cases of implant retained restorations to peri-implant bone destruction. Hence, we performed an in-vitro study to determine cytotoxicity of resin monomers on osteoblast-like cells. Methods: Three permanent osteoblast-like cell lines from tumor origin (MG-63 and Saos-2) as well as immortalized human fetal osteoblasts (hFOB 1.19) were used and treated with different concentrations of the main monomers: BisGMA, UDMA, TEGDMA and HEMA. The impact on cell viability was monitored using three different cytotoxicity tests: alamarBlue, XTT, and LDH assay. Mean ± SEM were calculated and statistical analysis was performed with GraphPad Prism software. Results: All monomers tested caused concentration dependent cytotoxic effects on the three investigated osteoblast-like cell lines. Although all three cell viability assays showed comparable results in cytotoxic ranking of the monomers (BisGMA > UDMA > TEGDMA > HEMA), higher differences in the absolute values were detected by the various test methods In addition, also a cell line dependent influence on cell viability could be identified with higher impact on the immortalized hFOB 1.19 cells compared to both osteosarcoma cell lines (MG-63, Saos-2). Conclusions: Monomer concentrations detected in elution studies caused toxic effects in osteoblast-like cells. Although the results from in-vitro studies cannot be directly transferred to a clinical situation our results indicate that released monomers from composite resin cements may cause adverse biological effects and thereby possibly lead to conditions favoring peri-implantitis and bone destruction. Clinical significance: The wide use of composite resin cements especially in implant-prosthetic treatments should be scrutinized to avoid possible clinical implications between eluted resin monomers and bone cells leading to conditions favoring peri-implantitis and bone destruction.